A novel method for copyright protection of digital videos using SWEA and ZPA technique - Ali, Jabir; Prakash Ghrera, Satya (International Journal of Engineering and Technology, 2018)
Digital copyright protection has become an effective way to prove the ownership and protect the multimedia contents from illegal use and unauthorized users. In order to prove the ownership of a video certain security program is embedded in a video and one of the ways of ensuring the ownership of a video is embedding the watermark in a video. In this paper, a new approach to digital video copyright protection, SWEA (Split watermark embedding algorithm) with Zero Padding Algorithm (ZPA) is proposed. With the help of this algorithm, it is hard to know the original pattern of watermark because of SWEA and minimizing the perceptual degradation of watermarked video because of ZPA. Here we are using ‘db1’ wavelet domain for embedding the watermark in the LL sub-band of the original identical frame (I-frame), based on the energy of high-frequency sub-band in an adaptive manner. SCD (Scene changed detection) is used to find out the identical frame (I-frame). The proposed algorithm has undergone various attacks, such as compression, uniform noise, Gaussian noise frame repetition and frame averaging attacks. The proposed algorithm, sustain all the above attacks and offers improved performance compared with the other methods from the literature.